2004
DOI: 10.1597/02-084
|View full text |Cite
|
Sign up to set email alerts
|

Social Interaction Patterns of Children and Adolescents with and without Oral Clefts during a Videotaped Analogue Social Encounter

Abstract: Differing patterns of overt social behavior as well as parent and self-perception can be measured between children with and without oral clefts. Such results may be helpful in developing interventions to enhance social skills and parent/child adjustment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 36 publications
0
26
0
Order By: Relevance
“…No differences between personality ratings given to children with clefts vs controls Slifer et al (2004) Children w/CLP (n = 23), CPO (n = 5), CLO (n = 6), and healthy controls (n = 34) …”
Section: Summary and Critiquementioning
confidence: 96%
See 1 more Smart Citation
“…No differences between personality ratings given to children with clefts vs controls Slifer et al (2004) Children w/CLP (n = 23), CPO (n = 5), CLO (n = 6), and healthy controls (n = 34) …”
Section: Summary and Critiquementioning
confidence: 96%
“…interviewed children about hypothetical social encounters and found that those with CFAs gave fewer "friendly"responses than did controls. In a recent observational study, Slifer et al (2004) found that children with clefts were less likely than controls to state a choice/preference during social interaction and to answer a peer's questions. The authors suggest that these features may reflect a passive and selfconscious pattern of interaction.…”
Section: Kappmentioning
confidence: 99%
“…Cleft lip and palate patients are more concerned with visible defects than with functional problems. However, keeping in mind that patients with repaired cleft lip and palate malformations feel as socially accepted as do peers without such malformations this low number of patients who decided to have corrective surgery is not surprising [19]. In addition, there are studies that show that patients with cleft lip and palate malformations seem to be relatively satisfied with their body image [8].…”
Section: Discussionmentioning
confidence: 99%
“…However, the data on psychosocial problems in this population are mixed (Slifer et al, 2004). For instance, a thorough review of the literature on psychosocial functioning in ICLP concluded that self-esteem is high among individuals with ICLP (Hunt et al, 2005).…”
Section: Introductionmentioning
confidence: 99%